Predicted occurrence of ancient coppice woodlands in the Czech Republic - Maděra, Petr; Machala, Martin; Slach, Tomáš; Friedl, Michal; Černušáková, Linda; Volařík, Daniel; Buček, Antonín (Italian Society of Silviculture and Forest Ecology, 2017)
Coppicing started in the Neolithic period and has been practiced throughout European history. This traditional silvicultural system was abandoned in many European countries during the 20th century. The Czech Republic now has a very low proportion of coppice woods (CW), as more than 1000 km2 CW were converted into high forests after World War II. Nevertheless, many CW were maintained as stored coppices, which could be the last remainders of ancient coppice woods (ACW) in the Czech Republic. Knowledge of area and distribution of stored coppices is currently missing in the Czech Republic, because they are recorded as high forests in forest management plans. Many stored forests are currently approaching the maturity age, with a high risk that these last ACW remainders will be lost; therefore, an inventory of ancient coppice woods is necessary. In our study, we develop an index of likelihood of coppice occurrence (COP) based on the distribution of habitats favourable for coppices, as well as on past and current occurrence of CW in the Czech Republic from historical maps. COP index values were then used to generate a map showing the relative likelihoods of occurrence of ACW, which can serve as a baseline to support the compilation of an ACW inventory and their mapping in the field. Our results can help prioritize forest areas to be inventoried based on their higher probabilities of ACW occurrence.
Keywords: Ancient Coppice Woodlands; Inventory; Coppice Occurrence; Cultural heritage